Det asketiske ideal: Iagttaget af Nietzsche og Foucault - Albinus, Lars (Religionsvidenskabeligt Tidsskrift, 2016)
This article presents a view of religious and philosophical asceticism in two prominent critics of modernity, Friedrich Nietzsche and Michel Foucault, who, despite obvious differences, agree on crucial points including the location of their own thinking within an ascetic ideal. However, where Nietzsche primarily attacks the ancient invention of asceticism as a self-renouncing will to truth among the weak, Foucault focuses on asceticism as ‘a practice of truth’ the goal of which is a creative exercise of self on self. Nevertheless, he does agree with Nietzsche that the element of self-improvement takes the form of self-renunciation in Christianity. Where Nietzsche, in this respect, reluctantly admits to being influenced by an ascetic culture, Foucault embraces asceticism as a way of life that manifests a subjective courage to truth independent of traditional values.